(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2018)
The aim of the paper is to analyze a source ‘ignored’ by local historiography: the cartulari of Guido Savina da Fogliano. Among the first cartularies (made by lords) to appeared in the Italian scene, those documents allow us to deepen the studies on the family which was one of the most important in Reggio during the 13th-14th centuries (and beyond). Made by Guido Savina, leading member of the Reggio Emilia family in the first three decades of the 14th century, the analysis of the cartularies offers a number of new points of view through which observe the history of the family: on one hand, the content of the document consolidates and extends what it is already known about the Fogliano. On the other hand, in the cartulary the history of the family is ‘disassembled in photograms’, which are then reshaped and rebuilt to show not just a simple chronology of family events, but rather to create a clear picture of the family and of its main member at that time. a speech, a storytelling made by goods, rights and privileges, in which the absolute protagonist is the family but, above all, Guido Savina da Fogliano. DOI 10.17464/9788867742721